1998
DOI: 10.1007/s007050050375
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of G serotype dependent non-antibody inhibitors of rotavirus in normal mouse serum

Abstract: Serotype specific (non-immunoglobulin) inhibitors of rotavirus have been identified in normal mouse serum obtained from BALB/c, CBA, and BL10 mice. Sialic acid was essential for the neutralising activity sera treated with the neuraminidase from Vibrio cholerae failed to neutralise rotavirus. G serotypes 4, 5, 7, 8, 9, and 10 were unaffected by the inhibitor(s) while G serotypes 1, 2, 6 and two G3 strains were neutralised to significant titres. Assessment of neutralisation of reassortants suggested that VP7 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…However, sialic acid binding does not appear to be essential for the infection of these rotaviruses, since sialic acid-independent mutants of RRV retain their infectivity (42). VP5* contains a long hydrophobic domain including a putative cell fusion region at amino acids (aa) 384 to 401 related by sequence to that of Sindbis virus (39).VP7 appears also to play a role in rotavirus cell attachment, since it has been identified as the infected cell lysate protein which bound to MA104 cell monolayers (52), and it may interact with VP4 to influence receptor-binding specificity (6,37,43).Previously, we have implicated integrins ␣2␤1, ␣4␤1, and ␣x␤2 in rotavirus cell entry (12). Integrins are ␣␤ heterodimeric, transmembrane glycoproteins important in cell adhesion and signalling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, sialic acid binding does not appear to be essential for the infection of these rotaviruses, since sialic acid-independent mutants of RRV retain their infectivity (42). VP5* contains a long hydrophobic domain including a putative cell fusion region at amino acids (aa) 384 to 401 related by sequence to that of Sindbis virus (39).VP7 appears also to play a role in rotavirus cell attachment, since it has been identified as the infected cell lysate protein which bound to MA104 cell monolayers (52), and it may interact with VP4 to influence receptor-binding specificity (6,37,43).Previously, we have implicated integrins ␣2␤1, ␣4␤1, and ␣x␤2 in rotavirus cell entry (12). Integrins are ␣␤ heterodimeric, transmembrane glycoproteins important in cell adhesion and signalling.…”
mentioning
confidence: 99%
“…VP7 appears also to play a role in rotavirus cell attachment, since it has been identified as the infected cell lysate protein which bound to MA104 cell monolayers (52), and it may interact with VP4 to influence receptor-binding specificity (6,37,43).…”
mentioning
confidence: 99%
“…Rotaviruses may enter either through an endocytotic pathway or through direct penetration. Although earlier studies implicated VP7 in cell attachment (19,46), recent studies have increasingly indicated that VP4 is the major player in the entry process (11,26,30) while VP7 may modulate the functions of VP4 (3,10,35,49).VP4 is susceptible to proteolysis and is cleaved by trypsin into VP8 ‫ء‬ (26 kDa) and VP5 ‫ء‬ (60 kDa). The two trypsin cleavage products remain associated with the virion, although the precise topographical locations of VP5 ‫ء‬ and VP8 ‫ء‬ in the VP4 spike are still uncertain.…”
mentioning
confidence: 99%
“…Rotaviruses may enter either through an endocytotic pathway or through direct penetration. Although earlier studies implicated VP7 in cell attachment (19,46), recent studies have increasingly indicated that VP4 is the major player in the entry process (11,26,30) while VP7 may modulate the functions of VP4 (3,10,35,49).…”
mentioning
confidence: 99%
“…The origins, cultivation in MA104 cells, and infectivity assay of human rotavirus strains Wa (G1P1A [8]), RV-5 (G2P1B [4]), RV-3 (G3P2A [6]), and S12/85 (G3P2A [6]); monkey rotavirus RRV (G3P5B [3]); bovine rotaviruses NCDV (G6P6 [1]) and UK (G6P7 [5]); and porcine rotaviruses CRW-8 (G3P9 [7]) and TFR-41 (G5P9 [7]) have been described previously (15,(45)(46)(47)(48). Reassortant rotaviruses 12-1 and 28-1 were produced and characterized previously (49).…”
Section: Methodsmentioning
confidence: 99%